The Association of Morning Hypertension With Target Organ Damage in Patients With Chronic Kidney Disease and Hypertension - Liu, Xiang; Li, Fangming; Zhang, Ting; Zheng, Zhiyao; Zhou, Huan; Qin, Aiya; Tang, Yi; Qin, Wei (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To determine the association between morning hypertension and target organ damage (TOD) in patients with chronic kidney disease (CKD) and hypertension. Methods: In this cross-sectional study, 447 patients with CKD and hypertension from two centers were enrolled. Ambulatory blood pressure monitoring was conducted in all patients. Linear regression and logistic regression analysis were used to determine the association between morning hypertension and TOD in patients with CKD and hypertension, including assessments of estimated glomerular filtration rate (eGFR), left ventricular mass index (LVMI), urine protein/creatinine ratio (UPCR), and left ventricular hypertrophy (LVH). Results: Overall, 194 (43.4%) participants had morning hypertension. Morning hypertension was strongly correlated with LVH [odds ratio (OR), 2.14; 95% confidence interval (CI), 1.3–3.51; p < 0.01], lower level of eGFR (β = −0.51; 95%CI, −0.95–−0.08; p < 0.05), higher LVMI (β = 0.06; 95%CI, 0.04–0.08, p < 0.001), and UPCR (β = 0.22; 95%CI, 0.06–0.38, p < 0.01), independent of nocturnal hypertension and elevated morning blood pressure surge. As a continuous variable, both morning systolic blood pressure (SBP) and diastolic blood pressure (DBP) were found to be associated with LVH and higher level of UPCR and LVMI (p < 0.05), whereas only morning SBP was negatively correlated with eGFR (p < 0.01). Conclusion: Morning hypertension was strongly correlated with cardiac damage and impaired kidney function in CKD patients with hypertension, independent of nocturnal hypertension and morning surge in blood pressure. Morning hypertension in CKD patients warrants further attention.